When differentiated empowering leadership hurts team performance: The roles of information sharing and tenure diversity. - Hu, Biyun; Han, Soojung; Harold, Crystal M.; D'Innocenzo, Lauren; Lee, Soojin (Human Relations, 2025)
The empowering leadership literature supports that empowering team members can result in a host of positive outcomes for work teams. These findings, however, largely assume that leaders uniformly empower their followers and overlook the potential consequences when leaders differentially empower members of the same team. In this study, we develop a theoretical model to delineate how and when differentiated empowering leadership affects team task performance. Drawing from social comparison theory, we position differentiated empowering leadership as adversely affecting team information sharing and subsequent team task performance. Moreover, we propose the indirect effect of differentiated empowering leadership on team task performance via team information sharing is conditional on organizational tenure diversity. To test our proposed model, we conducted a three-wave field study with 74 teams and their leaders from 17 South Korean firms. The results suggest that differentiated empowering leadership negatively affects team task performance through reduced team information sharing. This negative indirect effect was stronger in teams where organizational tenure diversity was low, compared with when it was high. The conclusions drawn from our research can help managers, HR professionals, and leadership coaches better understand and manage the complexities of empowering leadership to enhance team effectiveness.